The United States in the 1980’s - Conradie, D. (Scientia Militaria - South African Journal of Military Studies, 2011)
The era of optimism which prevailed in the United States since the Korean War, came to an abrupt end after the debacle in Vietnam. By the end of the Seventies the United States was no longer the dominant military power. American foreign policy lacked consistence, coherence and a strategic sense. The United States became indecisive. Under these circumstances the Soviet Union successfully enforced its imperialistic designs upon countries far from its shores.